ANALISIS TAKSONOMI BLOOM DAN KESUKARAN PADA BUTIR SOAL DI SD MA’ARIF NU 01 PANDANSARI - Maharani, Dita Tri Esti; Arifin, Ahmad; Puspita, Nela; Hidayat, Rahmany; Irma, Cintya Nurika (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
Evaluation is the process of using information to make judgements about how affectively a program has met students needs. In this study the authors examined the anallysis of Bloom’s taxonomy and the difficulty of the items. The level of difficulty is found in 2 quesstions, namely numbers 3 and 9 rejected and 28 questions are accepted. Researchers interviewed informants and observed the implementation of the program at SD Ma’arif NU 01 Pandansari. The learning program can be said to be successful if the learning objectives can be achieved. If students learning outcomes are more than a predetermined benchmark, then the learning program can be said to have been successful. And conversely if the learning outcomes have not been able to reach the standards applied, it can be said that the learning program has not been successful. Keywords: Bloom’s Taxonomy Analysis, Problem item Difficulty